Online Energy Management Strategy Based on Adaptive Model Predictive Control for Microgrid with Hydrogen Storage - Ma, Jun; Baysal, Mustafa (INT JOURNAL RENEWABLE ENERGY RESEARCH, 2018)
Energy management optimization is still a big challenge for Microgrid, which includes Renewable Energy and Hydrogen Fuel Cell. In this paper, an online Adaptive Model Predictive Control (AMPC) based Energy Management Strategy (EMS) is proposed to increase the energy sources lifetime of the microgrid while minimizing hydrogen consumption. The EMS problem is simplified according to the control structure of microgrid system and the cost function of system is built and transferred to standard format of the Quadratic Programming problem to solve. Moreover, adaptive algorithm is used to automatically adjust the weights of different targets according to the states of system. It is shown by simulation results for different cases from MATLAB-Simulink (TM) that proposed EMS has significant effects on controlling State-of-Charge (SoC) of battery and a noticeable improvement on extension of Hydrogen Fuel Cell lifetime and battery charge-sustainability.
Keywords: Adaptive Model Predictive Control; Hydrogen Fuel Cell; Microgrid; Online Energy Management Strategy; GENERATION SYSTEM; OPTIMIZATION; Energy & Fuels